ICT Convergence in Internet of Things – The Birth of Smart Factories - Hushairi, Zen; Adnan, Mahmood (IJCSIS, 2016)
Over the past decade, most factories across developed parts of the world employ a varying amount of the manufacturing technologies including autonomous robots, RFID (radio frequency identification) technology, NCs (numerically controlled machines), wireless sensor networks embedded with specialized computerized softwares for sophisticated product designs, engineering analysis, and remote control of machinery, etc. The ultimate aim of these all dramatic developments in manufacturing sector is thus to achieve aspects such as shorter innovation / product life cycles and raising overall productivity via efficiently handling complex interactions among the various stages (functions, departments) of a production line. The notion, Factory of the Future, is an unpredictable heaven of efficaciousness, wherein, issues such as the flaws and downtime would be issues of the long forgotten age. This technical note thus provides an overview of this awesome revolution waiting to be soon realized in the manufacturing sector.